Narration in V. Nabokovs' works : Ada, Tranparent things, look at the harlequins - Oumnih, Abou El Kacem (Université Mohamed 1er, Faculté des Lettres et des Sciences Humaines, Oujda, 2001)
In the present thesis, narration in Nabokov’s Transparent Things and look at the Harlequins. I have tried to analyze the fictional texts through various angles relating to narration. Throughout fourteen chapters i have attempted. 1) To demonstrate how the interaction between the narrator and the narrated object exhibits a confrotationnal relation of power ; 2) To tackle the narrator the perception/narration of transparent things ; 3) To exhibit the narrator responding to the evasive nature of objects through retrospective narration ; 4) To show differential play as a necessity of signification ; 5) To argue that autobiographical narration is pursuing signifying opportunities ; 6) To consider the complexity of narrating approaches to madness ; 7) To study the implied manifestation of some modes of perception ; 8) To tackle the manifestation of the process of construction ; 9) To demonstrate how emphasis on form may function as a parody of minetic narration ; 10) To show how mimetic narration is neither totally adhered to nor definitely rejected ; 11-12) To show that self-referring narration is a spur which stimulates unlimited signification ; 13) To consider the narrative manifestation of the impossibility of fulfiling exhaustive narration and finaly ; 14) To analyze some discursive manifestations of socialization
Keywords: Litterature; Narration; V. Nabokovs' work; Ada; Harlequin